2022
DOI: 10.3389/fphar.2022.932116
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Quantification of T2DM-Induced Mitochondrial Morphology Changes and Their Implications in Pharmacodynamics of Metformin and Sorafenib

Abstract: Mitochondria, as the powerhouse of cells, are involved in various processes of cellular homeostasis, especially energy metabolism. The morphology of mitochondria is a critical indicator for their functions, referring to mitochondrial fusion and fission. Here, we performed structured illumination microscopy (SIM) to measure the mitochondrial morphology in living cells. Benefitting from its nano-scale resolution, this SIM-based strategy can quantify the fusion and fission of mitochondria with high sensitivity. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that metformin enhances the antitumor effect of sorafenib by inhibiting the ferroptosis induced via the p62-Keap1-Nrf2 pathway [15] as well as the ATF4/STAT3 pathway [27]. In addition, metformin can also improve the e cacy of sorafenib by inhibiting mitochondrial ssion [17]. Another study found that the combination of sorafenib and metformin improves the recurrence and metastasis after liver resection in orthotopic mouse model [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that metformin enhances the antitumor effect of sorafenib by inhibiting the ferroptosis induced via the p62-Keap1-Nrf2 pathway [15] as well as the ATF4/STAT3 pathway [27]. In addition, metformin can also improve the e cacy of sorafenib by inhibiting mitochondrial ssion [17]. Another study found that the combination of sorafenib and metformin improves the recurrence and metastasis after liver resection in orthotopic mouse model [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the combination of metformin and sorafenib showed a synergistic effect in hepatocellular carcinoma cells in terms of induction of ferroptosis through the p62-Keap1-Nrf2 pathway [15], induction of autophagy, and inhibition of cell proliferation through the mTOR pathway [16]. Yang et.al [17] have suggested that metformin promotes the drug effect of sorafenib by inhibiting mitochondrial ssion. Other studies have also indicated that metformin may enhance the effect of sorafenib in inhibiting HCC recurrence and metastasis after liver resection by regulating the expression of HIF-2α and TIP30 [18].…”
Section: Introductionmentioning
confidence: 99%